The Impact of Organizational Commitment, Psychological Contracts and Job Satisfaction on Organizational Citizenship Behavior through Organization Expectancy: A Structural Equation Modeling Approach - Budiasih, Yanti; Rusmardiana, Ana (International Journal of Psychosocial Rehabilitation, 2020)
Behavior of employees is a crucial matter for any organization, as people usually devote 60 years of their life in the workplace. Organizational citizenship behavior (ORTCBH) is one of the most enquiring behavior. The current study aims to investigate the mediating role of organizational expectancy (OE) in the associations between organizational commitment (OGC) & ORTCBH, psychological contract (PSC) & ORTCBH and job satisfaction (JBS) & ORTCBH. Moreover, this study also investigates the moderating role of job stress (JST) in the relation between OE and ORTCBH. Findings reveal that OGC, PSC and JBS have significant positive impact on ORCTBH. OGC, PSC and JBS also have positive effect on OE. OE and JST have positive relation with ORTCBH. Findings of mediation reveal that OE fully mediates the relation between JBS and ORTCBH while partially mediates the association between OGC & ORTCBH and PSC & ORTCBH. Moreover, JST moderates the relationship between OE and ORTCBH. The findings suggest that there is a need to pay attention on expectative professional observations, and on the moderating role of JST in the affiliation between OE and ORTCBH as the JST creates negative state of job dissatisfaction.